Optimizing the Use of Heavy Equipment on Earthworks on the Syamsudin Noor Banjarbaru Airport Ring Road - Suwaji; Anisari, Rezky (Jurnal Multidisiplin Madani, 2024)
Earthworks on the Syamsudin Noor Banjarbaru Airport Ring Road Construction Project in 2019 include activities of digging, moving, displacing, leveling, forming the road body and compacting embankment soil in a loose volume of 375,000.00 m3 in solid with laterite soil type (chosen fill) . The heavy equipment used will be calculated for productivity, tool requirements and operational costs for each tool, namely: Komatsu PC 200 Excavator, Nissan Hino FM 260 JD 16 m3 Dump Truck, Catterpillar D6R Bulldozer, Catterpillar 120 G Motor Grader and Vibratory Roller Bomag Komatsu BW 217 D. Analysis and calculations using data analysis methods include material analysis, work implementation methodology, equipment production calculations, tool requirements, and equipment operating costs to complete the work. The results of the analysis show that Excavator productivity is 150.70 m3/hour, number of 3 units, operational costs Rp. .77m3/hour, number of 2 units, operational costs Rp. 1,617,521,830.24, Motor Grader productivity 1,392 m3 / hour, quantity 1 unit, operational costs Rp. 247,830,796, 12 and Vibratory Roller productivity 241.07 m3 / hour, number of 2 units, operational costs Rp. 757. 806,142.93. with a total cost of using heavy equipment for earthworks of Rp. 8,481,158,634.27